Destruction investigation of foundry sand-liquid-glass cores under compression - Y. I. Gutko; V. V. Voytenko (Литьë и металлургия)
Foundry sand cores based on organic binders have required tensile, compressive, and bending breaking points, as well as have an excellent knocking‑out ability. However, increased requirements for the environmental friendliness of the foundry have led to a renewed interest in foundry sand cores based on inorganic binders including the sand‑liquid‑glass core‑making technology. Foundry sand‑liquid‑glass cores are significantly inferior to foundry sand cores based on organic binders in terms of a knocking‑out ability due to using a sufficiently large mass fraction of sodium silicate solute to achieve required breaking points of foundry sand‑liquid‑glass cores under tension, compression, and bending, which is accompanied by a deterioration in a knocking‑out ability. Experimental studies aimed at selecting a composition of a sand‑liquid‑glass core mixture, which provides a required compressive breaking point of a foundry sand‑liquid‑glass core in combination with an improved knocking‑out ability, are carried out. Experimental results for destruction of foundry sand‑liquid‑glass cores under compression, which are showing a possibility of achieving a combination of a required compressive breaking point and a good knocking‑out ability, are presented. Ways to increase a strength of a foundry sand‑liquid‑glass core in places of contact with core locks, strengthen the most stressprone areas of a foundry core, and decrease its compressive breaking point by reducing a mass fraction of sodium silicate solute, thereby improving a knocking‑out ability, are considered. Structural robustness test results for foundry sand‑liquid‑glass cores of the investigated composition under compression, as well as an effect of adding a circulating core mixture to the composition on a compressive breaking point are discussed. An effect for inhomogeneities of a foundry sand‑liquid‑glass core on its compressive breaking point is presented. Mathematical expressions for calculating a destruction probability of a foundry core containing an inhomogeneity are obtained.